2007
DOI: 10.1007/s11138-007-0023-3
|View full text |Cite
|
Sign up to set email alerts
|

Freedom, barriers to entry, entrepreneurship, and economic progress

Abstract: Entrepreneurship, Creative destruction, Economic freedom, Barriers to entry, H11, L26, F13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 15 publications
2
73
0
3
Order By: Relevance
“…The 'innovation' or 'Schumpeterian' approach to economic growth suggests that markets tend toward disequilibrium as entrepreneurs contribute to the market's process of 'creative destruction' with new innovations replacing old technologies (Schumpeter 1934;Sobel et al 2007). Successful regional economies, therefore, are characterised as those associated with efficient innovation systems resulting from high levels of entrepreneurship, while weaker economies are those with failing innovation systems and lower levels of entrepreneurship .…”
Section: Entrepreneurship and Regional Innovationmentioning
confidence: 99%
“…The 'innovation' or 'Schumpeterian' approach to economic growth suggests that markets tend toward disequilibrium as entrepreneurs contribute to the market's process of 'creative destruction' with new innovations replacing old technologies (Schumpeter 1934;Sobel et al 2007). Successful regional economies, therefore, are characterised as those associated with efficient innovation systems resulting from high levels of entrepreneurship, while weaker economies are those with failing innovation systems and lower levels of entrepreneurship .…”
Section: Entrepreneurship and Regional Innovationmentioning
confidence: 99%
“…As already explained in the extant literature [16,33], regulatory constraints (e.g., enforcing contracts) could have a negative impact on TEA. Using a sample of twenty-seven Organization for Economic Cooperation and Development (OECD) member countries, Sobel et al [33] showed that barriers to entry and government regulation discourage people from starting a business.…”
Section: Hypothesis 1 (H1) Countries With Greater Access To Financiamentioning
confidence: 86%
“…Using a sample of twenty-seven Organization for Economic Cooperation and Development (OECD) member countries, Sobel et al [33] showed that barriers to entry and government regulation discourage people from starting a business. According to their results, 1% increase in the average tariff rate is associated with an 8% decrease in total entrepreneurial activity (TEA).…”
Section: Hypothesis 1 (H1) Countries With Greater Access To Financiamentioning
confidence: 99%
“…According to Schramm, the degree of economic fluidity has a direct effect on innovation and entrepreneurship. The positive connection between productive entrepreneurship and properly developed institutions is examined by Sobel, Clark and Lee (2007). The close connection between the different elements of economic freedom and that of GEM TEA index is provided in a recent study by McMullen et al (2008).…”
Section: Entrepreneurship-related Institutional/environmental Factorsmentioning
confidence: 99%